2022
DOI: 10.1002/cpt.2594
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Abrocitinib on Drug Transporters by Integrated Use of Probe Drugs and Endogenous Biomarkers

Abstract: Abrocitinib is an oral Janus kinase 1 (JAK1) inhibitor currently approved in the United Kingdom for the treatment of moderate-to-severe atopic dermatitis (AD). As patients with AD may use medications to manage comorbidities, abrocitinib could be used concomitantly with hepatic and/or renal transporter substrates. Therefore, we assessed the potential effect of abrocitinib on probe drugs and endogenous biomarker substrates for the drug transporters of interest. In vitro studies indicated that, among the transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Compared with formal (probe‐based) DDI studies, deployment of SLC biomarkers in most SAD‐MAD phase I studies will greatly facilitate calibration of an institution's in vitro data, especially if the growing list of published biomarker‐qualified perpetrator drugs is leveraged also. For example, during the writing of this manuscript, three NCEs (letermovir, PF‐06835919, and ipatasertib) were added to the list of biomarker (CPI)‐qualified perpetrators ( Table 1 ), clinical NMN data were reported for abrocitinib, which did not impact the plasma AUC (AUCR = 0.93) and CL renal (ΔCL renal <5%) of metformin ( Table , Figure ), and a static model was described for bridging CPI to substrates such as statins 41,101–104 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with formal (probe‐based) DDI studies, deployment of SLC biomarkers in most SAD‐MAD phase I studies will greatly facilitate calibration of an institution's in vitro data, especially if the growing list of published biomarker‐qualified perpetrator drugs is leveraged also. For example, during the writing of this manuscript, three NCEs (letermovir, PF‐06835919, and ipatasertib) were added to the list of biomarker (CPI)‐qualified perpetrators ( Table 1 ), clinical NMN data were reported for abrocitinib, which did not impact the plasma AUC (AUCR = 0.93) and CL renal (ΔCL renal <5%) of metformin ( Table , Figure ), and a static model was described for bridging CPI to substrates such as statins 41,101–104 …”
Section: Discussionmentioning
confidence: 99%
“…For example, during the writing of this manuscript, three NCEs (letermovir, PF-06835919, and ipatasertib) were added to the list of biomarker (CPI)-qualified perpetrators (Table 1), clinical NMN data were reported for abrocitinib, which did not impact the plasma AUC (AUCR = 0.93) and CL renal (ΔCL renal <5%) of metformin (Table S2, Figure 3b, Figure 6b), and a static model was described for bridging CPI to substrates such as statins. 41,[101][102][103][104] Currently, the International Council for Harmonization (ICH) Executive Working Group is working on the development of a new guidelines (document ICH M12) with a view to providing a consistent approach to the design, conduct, and interpretation of DDI studies (https://www.ich.org/page/multi disci plina ry-guide lines). Within the draft ICH M12 documentation, SLC biomarkers are briefly described.…”
Section: Reviewmentioning
confidence: 99%
“…The importance of OATP1B transporters in the hepatic uptake of CPI and CPIII was also demonstrated by Shen et al, 17 who showed that itraconazole and diltiazem, strong and moderate inhibitors, respectively, of cytochrome P450 (CYP) 3A4, did not affect CPI exposures, consistent with the expected lack of significant effect of these inhibitors on OATP1B1 transporters. It is important to note that, although an extensive discussion of other endogenous biomarkers for OATP1B and endogenous biomarkers for transporters other than OATP1B is outside the scope of this brief report, there are ongoing efforts to characterize endogenous biomarkers for assessing other uptake transporters such as OAT1, OAT3, and OCT2 and efflux transporters such as MATE‐1/2K 7,18–20 …”
Section: Expanding the Ddi Assessment Toolkit With Endogenous Biomarkersmentioning
confidence: 99%
“…It is important to note that, although an extensive discussion of other endogenous biomarkers for OATP1B and endogenous biomarkers for transporters other than OATP1B is outside the scope of this brief report, there are ongoing efforts to characterize endogenous biomarkers for assessing other uptake transporters such as OAT1, OAT3, and OCT2 and efflux transporters such as MATE-1/2K. 7,[18][19][20] Integrating Endogenous Biomarkers Early in Drug Development to Streamline DDI Assessments and Facilitate Mechanistic Understanding of Complex DDIs Assessing transporter biomarkers in single-and multiple-ascending-dose ranging trials, where a wide range of doses are generally evaluated may help to streamline and prioritize subsequent DDI trials. 21 The magnitude of change in the concentrations of CPI and CPIII has not only been demonstrated to be dose dependent for a given inhibitor but also sensitive to the potency of the OATP1B1 inhibitor, underscoring the potential utility of assessing CPI and CPIII early in development.…”
Section: Expanding the Ddi Assessment Toolkit With Endogenous Biomarkersmentioning
confidence: 99%
“…[3][4][5][6] Alternatively, monitoring the concentrations of endogenous biomarkers for relevant transporters during phase I clinical trials has been increasingly used as a surrogate measure of transporter DDIs. [7][8][9] Such biomarker data, coupled with physiologically-based pharmacokinetic (PBPK) modeling, could enable an accurate assessment of the in vivo DDI risk of an NCE and guide the decision on necessity for a dedicated DDI study. 10 Several PBPK models for endogenous biomarkers have already been developed, verified, and applied to estimate the in vivo transporter inhibitory potential of selected inhibitors, 9,11 understand the impact of transporter genotype on endogenous biomarkerinformed DDI assessment, 12 and disease-related changes in biomarker levels.…”
mentioning
confidence: 99%